INTERNALIZATION OF ANTIMICROBIAL PEPTIDE ACIPENSIN 1 INTO HUMAN TUMOR CELLS - E. S. Umnyakova; I. V. Kudryavtsev; N. A. Grudinina; S. V. Balandin; I. A. Bolosov; P. V. Panteleev; T. A. Filatenkova; D. S. Orlov; E. V. Tsvetkova; T. V. Ovchinnikova; V. N. Kokryakov; O. V. Shamova (Медицинская иммунология)
Search for new compounds providing delivery of drugs into infected or neoplastic cells, is an important direction of biomedical research. Cell-penetrating peptides are among those compounds, due to their ability to translocate through membranes of eukaryotic cells, serving as potential carriers of various therapeutic agents to the target cells. The aim of present work was to investigate the ability of acipensin 1, an antimicrobial peptide of innate immune system, for in vitro penetration into human tumor cells. Acipensin 1 is a cationic peptide that we have previously isolated from leukocytes of the Russian sturgeon, Acipenser gueldenstaedtii. Capability of acipensin 1 to enter the human erytroleukemia K-562 cells has been investigated for the first time. A biotechnological procedure for producing a recombinant acipensin 1 peptide has been developed. The obtained peptide was conjugated with a fluorescent probe BODIPY FL. By means of confocal microscopy, we have shown that the tagged acipensin 1 rapidly enters into K-562 cells and can be detected in the intracellular space within 5 min after its addition to the cell culture. Using flow cytometry technique, penetration kinetics of the labeled peptide into K-562 cells (at nontoxic micromolar concentrations) has been studied. We have observed a rapid internalization of the peptide to the target cells, thus confirming the results of microscopic analysis, i.e, the labeled acipensin was detectable in K-562 cells as soon as wihin 2-3 seconds after its addition to the incubation medium. The maximum of fluorescence was reached within a period of approx. 45 seconds, with further “plateau” at the terms of >100 seconds following cell stimulation with the test compound. These data support the concept, that the antimicrobial peptides of innate immunity system possess the features of cell-penetrating peptides, and allow us to consider the studied sturgeon peptide a promising template for development of new drugs with increased ability to enter the cells implicated into pathological processes, and, therefore, higher therapeutic efficiency.